THE CORRELATION BETWEEN WET AND DRY WEIGHT OF INTESTINE AND BODY WITHOUT INTESTINE OF SEA CUCUMBER (Holothuria scabra) - Lisa Fajar Indriana; Andreas Kunzmann (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
Holothuria scabra is a commercial tropical sea cucumber species, which has been exploited severely in recent years. This study was conducted at the Mataram Marine Bio Industry Technical Implementation Unit for 20 days aiming to determine the relationship between wet and dry weight of sea cucumbers with and without colon. Results of regression analysis between wet and dry weight show a significant positive correlation. The relationship between wet and dry weight without the colon is y = 0.1685x – 0.2319 (R2 = 0.9236) whereas the wet and dry wet of the intestine is y = 0.075x + 0033 (R2 = 0.791).